Synergy in the Fulfilment of National Interest in Efforts to Handle Refugees in Indonesia through Repratiation and Resettlement - Widagdo, Setyo; Ikaningtyas, Ikaningtyas; Susanto, Fransiska A.; Hidayat, M. Choirul (Brawijaya Law Journal : Journal of Legal Studies, 2021)
This article aims to analyze Indonesia's efforts to accommodate national interests in efforts to handle refugees in Indonesia. UNHCR noted that until December 2020 the number of refugees in Indonesia reached 13,700 people, with the most refugees coming from Afghanistan 57%, Somalia 10%, and Myanmar 7%. This number is very large considering the fact that Indonesia is only a transit country and not a country that ratified the 1951 Refugee Covenant. The existence of refugees in Indonesia is an urgent problem by taking advantage from human rights as the basis of its justification, while Indonesia is a sovereign country that has the authority to regulate the traffic of foreigners in its territory especially on the basis of national interests, such as security. The existence of Presidential Regulation No. 125/2016 on the Handling of Refugees from Abroad has not optimally become a solution for handling refugees in Indonesia. By using normative juridical research method, the authors analyzed that although the regulations regarding repatriation and resettlement of refugees were mentioned in Presidential Regulation No. 125/2016, they did not clearly regulate the procedures for handling refugees either through voluntary repatriation and there was no attempt by the government to implement the repatriation program. As for resettlement, the Indonesian government only relies on UNHCR